A Carbon Monoxide Poisoning Case in Which Hyperbaric Oxygen Therapy Was Not Possible Due to Iatrogenic Pneumothorax after Unnecessary Central Catheterization - Hyung Il Kim; Seong Beom Oh (Journal of Trauma and Injury)
Hyperbaric oxygen therapy (HBOT) is used to treat carbon monoxide (CO) poisoning. However, untreated pneumothorax is an absolute contraindication for HBOT. More caution is needed with regard to monoplace hyperbaric chambers, as patient monitoring and life-saving procedures are impossible inside these chambers. Central catheterization is frequently used for various conditions, but unnecessary catheterization must be avoided because of the risk of infection and mechanical complications. Herein, we describe a case of CO poisoning in which iatrogenic pneumothorax developed after unnecessary subclavian central catheterization. The patient did not need to be catheterized, and HBOT could not be performed because of the pneumothorax. Hence, this case reminds us of basic—but nonetheless important—principles of catheterization.